Risk Factors for Recurrent Intussusception in Children: A Systematic Review and Meta-Analysis - Ye, Xiaohua; Tang, Rong; Chen, Shangqin; Lin, Zhenlang; Zhu, Jianghu (Frontiers in Pediatrics, 2019)
Background: Intussusception is a common abdominal emergency in infancy and childhood, and the recurrence rate is reported to be up to 20%. Numerous potential risk factors for recurrence have been reported, although some of them are still controversial. Objective: The present study was conducted to identify the risk factors or predictive symptoms for recurrent intussusception in children who successfully recovered via enema reduction. Methods: The databases of PUBMED, EMBASE, and Cochrane were searched up to August 2018. The primary outcome was the odds ratio involving the following potential risk factors: sex, the presence of blood in stool, fever, abdominal pain, right abdominal mass, pathological lead point, and vomiting. Results: A total of 12008 participants from 10 studies included in the abovementioned databases were enrolled in this meta-analysis. The correlation strength with each risk factor was as follows: Sex (OR = 0.87 [0.69, 1.09], P = 0.22)); fever (OR = 1.85 [1.29, 2.65], P = 0.0008); blood in stool (OR = 0.93 [0.52, 1.67], P = 0.25); abdominal pain (OR = 0.82 [0.49, 1.37], P = 0.46); vomiting (OR = 0.55 [0.37, 0.80], P = 0.002); pathological lead point (PLP) (OR = 7.71 [1.96,30.29], P = 0.003); location of the mass (OR = 0.51 [0.03, 8.28], P = 0.64). Besides, children who were relatively older (over 1 to 2 years of age) were seen to have a higher risk of recurrence. Conclusion: The main conclusion of this meta-analysis was that children with the presence of fever and PLP may have a higher risk of recurrence following enema reduction for intussusception. The prevalence of vomiting was found to be lower in RI (Recurrent Intussusception) patients than in the non-RI patients (control group).